Kecerdasan Logis Matematis Siswa MA Dalam Menyelesaikan Masalah Matriks - Muhammad Wahid Romadhon; wildan hakim (CONSISTAN (Jurnal Tadris Matematika), 2025)
Mathematical logical intelligence is intelligence related to inductive and deductive thinking, logical reasoning, and students' problem-solving skills, this intelligence affects students' ability to solve math problems. The purpose of this research is to describe the mathematical logical intelligence of MA students in solving matrix problems. The research method used is descriptive qualitative. The subjects in this study were XI grade students of MA Raudlatul Ulum Putra Gondanglegi, researchers used purposive sampling in collecting research subjects. The data collection techniques used by researchers are test, interview, and documentation methods. Reduction, data presentation, and conclusion drawing were used by researchers in data analysis. The results showed that students with high mathematical logical intelligence category could fulfill 4 indicators at once, namely: perform various mathematical operations, understand patterns and relationships, think logically, and think systematically. Students with moderate mathematical logical intelligence category were only able to fulfill 3 of the 4 indicators, namely: performing various mathematical operations, understanding patterns and relationships, and thinking logically. Meanwhile, students with low mathematical logical intelligence category were only able to fulfill a maximum of 2 indicators, namely performing various mathematical operations and thinking logically words.